KEDUDUKAN SERTIPIKAT ELEKTRONIK DALAM KEPEMILIKAN HAK ATAS TANAH - Salatun, Novalin; Marzuki, Abdul Ukas; Mina, Risno; Labatjo, Ridwan (Fakultas Hukum Universitas Muhammadiyah Luwuk, 2025)
Electronic-based land services must be implemented to optimize the use of information and communication technology in today's digital era. The purpose of this study is to determine how the process of issuing land certificates electronically is carried out and how the electronic certificate law functions based on positive law in Indonesia. The type of normative legal research is a type of research that focuses on positive legal norms, such as laws and regulations and expert opinions. The steps in the process of issuing land certificates electronically include submitting applications, verifying documents, measuring and mapping, issuing certificates, and storing and managing electronic certificates. Meanwhile, electronic certificates and physical certificates are legally considered valid evidence of ownership of land rights, and both have the same legal authority and can be used in various legal transactions and land dispute resolution, with the support of digital signatures that guarantee the authenticity and integrity of documents